2004
DOI: 10.1103/physreve.70.025101
|View full text |Cite
|
Sign up to set email alerts
|

Modularity from fluctuations in random graphs and complex networks

Abstract: The mechanisms by which modularity emerges in complex networks are not well understood but recent reports have suggested that modularity may arise from evolutionary selection. We show that finding the modularity of a network is analogous to finding the ground-state energy of a spin system. Moreover, we demonstrate that, due to fluctuations, stochastic network models give rise to modular networks. Specifically, we show both numerically and analytically that random graphs and scalefree networks have modularity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
671
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 805 publications
(695 citation statements)
references
References 24 publications
18
671
2
4
Order By: Relevance
“…The level of community structure decreases until it is comparable to that of a random network of equivalent size and density [16]. However, while social ties are distributed more homogeneously throughout the population for TAE capacity above two, they are more likely to be between similar individuals.…”
Section: Series A: Increasing Individual Tae Capacitymentioning
confidence: 98%
“…The level of community structure decreases until it is comparable to that of a random network of equivalent size and density [16]. However, while social ties are distributed more homogeneously throughout the population for TAE capacity above two, they are more likely to be between similar individuals.…”
Section: Series A: Increasing Individual Tae Capacitymentioning
confidence: 98%
“…Modularity has been very influential in the recent community detection literature [128,53], and one can use spectral techniques to approximate it [157,131]. On the other hand, Guimerà, Sales-Pardo, and Amaral [85] and Fortunato and Barthélemy [73] showed that random graphs have high-modularity subsets and that there exists a size scale below which communities cannot be identified. In part as a response to this, some recent work has had a more statistical flavor [86,140,144,94,133].…”
Section: Relationship With Community Identification Methodsmentioning
confidence: 99%
“…For example, it has been found that even random graphs can have good modularity scores [85]. Intuitively, random graphs have no community structure, but there can still exist sets of nodes with good community scores, at least as measured by modularity (due to random fluctuations about the mean).…”
Section: Connections and Broader Implicationsmentioning
confidence: 99%
“…Eq. (1) alleviates this problem by imposing the constraint that M is zero if the nodes are randomly located across the modules, or if all nodes belong to the same cluster [16,17].…”
Section: Community Detectionmentioning
confidence: 99%
“…Modularity-based measures have been proposed for community detection [16][17][18]. Given a partition of a complex network into modules (sub-networks), the network modularity, M quantifies the strength of the division as:…”
Section: Community Detectionmentioning
confidence: 99%